GENETIC VARIABILITY AND CORRELATION STUDIES IN BIRD OF PARADISE GENOTYPES FOR FLOWER AND YIELD PARAMETERS DURING 2011 - AIRADEVI P. ANGADI; B. ARCHANA (The Bioscan, 2014)
Experiment was conducted to study the genetic variability and association among the yield component traits in Bird of paradise. All the genotypes showed considerable amount of variation in their mean performances with respect to the characters studied, indicates presence of sufficient variability and scope for further selection and breeding superior and desirable genotypes. Large differences between GCV and PCV were observed in flower stalk girth (19.73 and 23.15%), vase life (19.92 and 21.71%) and number of bracts (39.04 and 42.64%), indicating the role of environment in expression of these traits. The magnitude of variability parameters were all high for suckers/hill (2.80 and 3.44) compared to flowers/hill (0.57 and 1.07), indicating wide variability for suckers/hill. All flowering characters exhibited high heritability coupled with high genetic advance over per cent mean indicating the predominance of additive components. Thus direct selection helps in improving the characters. Number of flowers per hill showed positive and significant correlations with plant height (0.478 and 0.293), stem girth (0.283 and 0.172), leaf width (0.204 and 0.162), leaf length (0.568 and 0.291), number of leaves per plant (0.640 and 0.275) and number of suckers per hill (0.766 and 0.976) at genotypic and phenotypic levels. Among the genotypes studied, number of suckers exhibited significantly high positive association with number of flowers. Thus, suggesting the possibility of simultaneous selection for this character.